Specificity of basic information processing and inhibitory control in attention deficit hyperactivity disorder. Issue 3 (8th April 2013) - Salum, G. A.; Sergeant, J.; Sonuga-Barke, E.; Vandekerckhove, J.; Gadelha, A.; Pan, P. M.; Moriyama, T. S.; Graeff-Martins, A. S.; de Alvarenga, P. Gomes; do Rosário, M. C.; Manfro, G. G.; Polanczyk, G.; et al.
Abstract : Background: Both inhibitory-based executive functioning (IB-EF) and basic information processing (BIP) deficits are found in clinic-referred attention deficit hyperactivity disorder (ADHD) samples. However, it remains to be determined whether: (1) such deficits occur in non-referred samples of ADHD; (2) they are specific to ADHD; (3) the co-morbidity between ADHD and oppositional defiant disorder/conduct disorder (ODD/CD) has additive or interactive effects; and (4) IB-EF deficits are primary in ADHD or are due to BIP deficits. Method: We assessed 704 subjects (age 6–12 years) from a non-referred sample using the Development and Well-Being Assessment (DAWBA) and classified them into five groups: typical developing controls (TDC; n = 378), Fear disorders ( n = 90), Distress disorders ( n = 57), ADHD ( n = 100), ODD/CD ( n = 40) and ADHD+ODD/CD ( n = 39). We evaluated neurocognitive performance with a Two-Choice Reaction Time Task (2C-RT), a Conflict Control Task (CCT) and a Go/No-Go (GNG) task. We used a diffusion model (DM) to decompose BIP into processing efficiency, speed–accuracy trade-off and encoding/motor function along with variability parameters. Results: Poorer processing efficiency was found to be specific to ADHD. Faster encoding/motor function differentiated ADHD from TDC and from fear/distress whereas a more cautious (not impulsive) response style differentiated ADHD from both TDC and ODD/CD. The co-morbidity between ADHD and ODD/CD reflected only additive effects. All ADHD-related IB-EF classical effects were fully moderated by deficits in BIP. Conclusions: Our findings challenge the IB-EF hypothesis for ADHD and underscore the importance of processing efficiency as the key specific mechanism for ADHD pathophysiology.